2007
DOI: 10.1002/art.22763
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of videotaped objective structured clinical examination in the assessment of joint examination skills of medical students

Abstract: Objective. Objective structured clinical examination (OSCE) is a key part of medical student assessment. Currently, assessment is performed by medical examiners in situ. Our objective was to determine whether assessment by videotaped OSCE is as reliable as live OSCE assessment. Methods. Participants were 95 undergraduate medical students attending their musculoskeletal week at Freeman Hospital, Newcastle (UK). Student performance on OSCE stations for shoulder or knee examinations was assessed by experienced rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…The calculated ICC values considering all raters indicated that there were variations in scoring. It should be noted that although we consider our ICCs as moderate, discrepancies exist across studies for ICC interpretation [5,13,25,26,27,28]. Consistent with our findings, the literature has shown interrater reliability between video and direct scoring to be moderate or higher [3,13,18].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The calculated ICC values considering all raters indicated that there were variations in scoring. It should be noted that although we consider our ICCs as moderate, discrepancies exist across studies for ICC interpretation [5,13,25,26,27,28]. Consistent with our findings, the literature has shown interrater reliability between video and direct scoring to be moderate or higher [3,13,18].…”
Section: Discussionsupporting
confidence: 81%
“…We surmise that an intensified mandatory rater training would have increased interrater consistency in scoring and thus improved the ICCs. Data from Vivekananda et al [13] suggest that video scores are reproducible and provide high intrarater reliability. We provide no evidence to support or oppose this, but find it likely to be true, considering the fact that we found direct OSATS and video OSATS ratings to have high internal consistency between GRS and STS scores, as calculated by Cronbach's α.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Video shooting and learning in the modern education ease the student's attention and interactions. Videotaped station can be a standard practical assessment procedure in marking, even with off campus examiners, and is also useful to retrieve the evidence of students' performance in future [9]. Experts had mentioned in early studies to modify the OSPE procedures based on local circumstances in educational institutes [8].…”
Section: Introductionmentioning
confidence: 99%
“…5 Vivekananda-Schmidt and colleagues investigated inter-rater reliability between real-time and video-recorded OSCEs of 95 third-year medical students' shoulder and knee examinations using the intraclass correlation coefficient (ICC). 5 Real-time OSCE encounters were scored by physicians training in rheumatology who were present in the room with the student and standardized patient during the encounter. Later, a consultant rheumatologist observed a video recording of the encounter and independently scored each student's performance.…”
Section: Introductionmentioning
confidence: 99%